ANALISIS PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM PEMBELAJARAN PKn DI SEKOLAH DASAR - Sulaimah, Esti; Wibawa, Sutrisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Researchers want to examine in more depth how the Project Based Learning learning model is applied in Civics learning in elementary schools, with the aim of analyzing and describing in more detail the application of the Project Based Learning learning model that has been implemented. The research approach used is qualitative with a literature study or literature review type of research. The stages used in this research design include focusing on scientific articles, data collection, data analysis, and conclusions. The results of this research are that the application of the Project Based Learning Model can improve student learning outcomes, increase student understanding of the material in Civics learning, foster student creativity and student self-confidence. It is hoped that this article can make practitioners better understand the benefits of implementing the Project Based Learning learning model in Civics learning in elementary schools.